Cardiovascular responses to metipranolol and timolol eyedrops in healthy volunteers. - Bacon, P J (1989)
1. Intraocular pressure and cardiovascular responses to metipranolol 0.1% and 0.3% and timolol 0.25% eyedrops were measured in a balanced single dose placebo-controlled crossover study in eight healthy volunteers aged 34-58 years. 2. Timolol 0.25% and metipranolol 0.3% reduced intraocular pressure throughout the 6 h period of observation to a similar extent. Metipranolol 0.1% was marginally less effective, significantly reducing pressure up to 4 h only. 3. No drug treatment significantly altered resting heart rate or blood pressure. Timolol 0.25% significantly reduced exercise tachycardia (P less than 0.05), an effect which was not shown by metipranolol 0.1 or 0.3%. Exertional pain in the legs occurred more frequently after timolol 0.25% and metipranolol 0.3% than after metipranolol 0.1% or placebo eyedrops. 4. Octan-1-ol/pH 7.4 buffer distribution coefficients at 37 degrees C were found to be: metipranolol 5.19, timolol 0.84, indicating that metipranolol has an approximately 6-fold greater lipid solubility. 5. It is concluded that, by comparison with timolol, metipranolol in eyedrop concentrations up to 0.3%, despite its greater lipid solubility, reaches concentrations in the systemic circulation which are less likely to affect the heart.